Effects of herpes simplex virus on mRNA stability. - Strom, T (1987)
Herpes simplex virus virions contain one or more functions which mediate shutoff of host protein synthesis, disaggregation of host polyribosomes, and degradation of host mRNA. We studied aspects of the host shutoff mechanism by using herpes simplex virus type 1 mutants deficient in virion-induced shutoff of host protein synthesis (G. S. Read and N. Frenkel, J. Virol. 46:498-512, 1983). Shutoff of host protein synthesis by the wild-type virus was associated with degradation of host mRNAs, including beta-actin, alpha-tubulin, and heat shock protein 70. In contrast, the virion host shutoff (vhs) mutants were deficient to various degrees in their ability to induce host mRNA degradation; the extent of mRNA degradation correlated well with the extent of inhibition of host protein synthesis. This finding suggests that inhibition of host protein synthesis and degradation of host mRNA were mediated by the same virion-associated function. Virion-induced degradation of host mRNA was not prevented by inhibitors of ribosome translocation, nor could it be augmented, for mutant vhs-1, by drugs which disaggregate polyribosomes. This suggests that mRNA in polyribosomes, as well as nonpolyribosomal mRNA, is susceptible to virion-induced degradation. Finally, the half-life of viral transcripts was also prolonged in cells infected with the vhs-1 mutant virus, suggesting that the vhs function indiscriminately decreased the half-lives of both host and viral mRNAs. The vhs function may thus play a dual role in virus infection. (i) It inhibits host gene expression, and (ii) it enables rapid transitions in the expression of viral genes which are sequentially transcribed as infection progresses.